2019
DOI: 10.1038/s41598-019-41146-9
|View full text |Cite
|
Sign up to set email alerts
|

Interactive influences of intercropping by nitrogen on flavonoid exudation and nodulation in faba bean

Abstract: In order to address the question of how flavonoids affected root nodulation of faba bean in a wheat and faba bean intercropping system, we set up soil and hydroponic experiments comprising two cropping pattern treatments (intercropped and monocropped) and three nitrogen (N) supply treatments at the deficient (50% N), adequate (100% N), and excessive (150% N) levels with three replicates in a randomized complete block design. Across the three N treatments and two experiments, it was frequently observed that int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
(47 reference statements)
2
22
1
2
Order By: Relevance
“…Then, improved nodulation of soybean in intercropping under P deficient condition facilitated the growth of soybean and neighbouring maize (Table .1). Our results were in line with other previous studies on legume/cereal intercropping systems such as faba bean/wheat [24] , faba bean/maize [22] and pea/maize [23] in terms of nodulation and N 2 fixation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Then, improved nodulation of soybean in intercropping under P deficient condition facilitated the growth of soybean and neighbouring maize (Table .1). Our results were in line with other previous studies on legume/cereal intercropping systems such as faba bean/wheat [24] , faba bean/maize [22] and pea/maize [23] in terms of nodulation and N 2 fixation.…”
Section: Discussionsupporting
confidence: 93%
“…A large number of results derived from field and pot experiments have proved that intercropping of legume and cereal could enhance the efficient utilization of phosphorus and yield through interspecific facilitation, even under phosphorus deficient conditions [18][19][20][21] . Additionally, evidences had accumulated recently that the practice of intercropped legume with cereal promoted the nodulation and N 2 fixation of legume by interspecific facilitation, and resulted in increased N uptake of associated cereal [22][23][24] . Considering the interspecific facilitation, we hypothesized that P level in nodules of legume under P stressful environment would be stimulated by intercropping.…”
Section: Introductionmentioning
confidence: 99%
“… 29 These results are consistent with the findings from previous experiments conducted both in soil and hydroponic systems, showing that co-cultivation between cereal and legumes significantly increased the concentration of flavonoids in legume root exudate and promoted nodulation in legumes. 24 , 36 Li et al, 2009, reported that soil nitrogen deficiency could stimulate the biosynthesis of nod-inducer flavonoids and regulate their release into the root zone through the mechanism known as negative feedback regulation of nitrogen. 35 When legumes are used in intercropping systems with a cereal, rhizosphere N availability decreases during the first growing stages because of the stronger competition of cereals for nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies revealed that interactions between plant species depend mainly on resource competition, 4 , 24 but there is increasing evidence showing involvement of allelochemicals. 37 , 38 Also, when optimal nutritional conditions occur, plants sense and respond to neighboring plants’ roots by changing the chemical profile of their root and root exudates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, legume (Fabaceae) crops may represent such key species, because they are known to be important in agroecosystem productivity and stability (Spehn et al, 2002). Normally, leguminous crops fix nitrogen (N) through symbiotic azotobacteria (Mosier, 2002;Yingchao et al, 2019) and provide additional nutrients to nearby crops (Chu, Shen & Cao, 2004;Xin-Ping Chen et al, 2011), and as a consequence, leaf nitrogen concentration in neighboring crops is affected (Temperton et al, 2007). However, drought negatively affects symbiotic nitrogen fixation by leguminous crops, through reduced phloem flow that facilitates nitrogenase activity in nitrogenated nodules (Marino et al, 2007;Serraj, Sinclair & Purcell, 1999).…”
Section: Introductionmentioning
confidence: 99%